Pengaruh EVA Dan MVA Terhadap Return Saham Perusahaan Food & Beverage di BEI - Riszka Utami, Aisyah; Elmira Siska; Natal Indra (BADAN PENERBIT STIEPARI PRESS, 2023)
This study aims to determine the effect of Economic Value Added (EVA) and Market Value Added (MVA) on stock returns in Food and Beverage companies listed on the Indonesia Stock Exchange. The method used for data collection is a documentation technique by obtaining company financial report data, which can be accessed via www.idx.co.id. The research method used is a statistical quantitative method with data collection techniques using purposive sampling with a total sample of 26 companies. Data processing uses the SPSS 22 program which includes classic assumption tests, descriptive statistics, partial tests and simultaneous tests. The results of the t test show that EVA has a positive but not significant effect on stock returns. MVA has a positive but not significant effect on stock returns. The F test shows that EVA and MVA have a positive and significant effect on stock returns.